Multicentre study of laparoscopic or open assessment of the peritoneal cancer index (BIG‐RENAPE). (26th March 2018) - Passot, G.; Dumont, F.; Goéré, D.; Arvieux, C.; Rousset, P.; Regimbeau, J.‐M.; Elias, D.; Villeneuve, L.; Glehen, O.; ,
Abstract : Background: The peritoneal cancer index (PCI) is a comparative prognostic factor for colorectal peritoneal metastasis (CRPM). The ability of laparoscopy to determine the PCI in consideration of cytoreductive surgery remains undetermined, and this study was designed to compare it with laparotomy. Methods: A prospective multicentre study was conducted for patients with no known CRPM, but at risk of peritoneal disease. Surgery began with laparoscopic exploration followed by open exploration to determine the PCI. Concordance between laparoscopic and open assessment was evaluated for the diagnosis of CRPM and for the PCI. Results: Among 50 patients evaluated, CRPM recurrence was found in 29 (58 per cent) and 34 (68 per cent) at laparoscopic and open surgery respectively. Laparoscopy was feasible in 88 per cent (44 of 50) and deemed satisfactory by the surgeon in 52 per cent (26 of 50). Among the 25 evaluable patients with satisfactory laparoscopy, there was concordance of 96 per cent (24 of 25 patients) and 38 per cent (10 of 25) for laparoscopic and open assessment of CRPM and the PCI respectively. Where there were discrepancies, it was laparoscopy that underestimated the PCI. Conclusion: Laparoscopy may underestimate the extent of CRPM. Abstract : Underestimated by laparoscopy